Le récit de l’exil dans l’écriture romanesque d’Atiq Rahimi - Rollo, Alessandra (Ponti/Ponts, 2022)
Exile as a theme is widely echoed throughout Francophone literature where the feeling of uprooting from one’s native land reverberates – a feeling that heightens nostalgia and fuses identity, while stimulating literary creativity to express wandering and heartbreak. In this paper, we wish to reflect on how Franco-Afghan writer Atiq Rahimi addresses exile in his two latest books, La Ballade du calame (2015) and Les Porteurs d’eau (2019). We aim to examine the writing process, investigating the relationship with language in building the narrative of an exiled life through which to share one’s existential wounds and at the same time reveal a revival: writing as a remedy for melancholy. On the one hand, we see exile portrayed through callimorphism – an interweaving of text and drawn words – testifying to a quest for identity and the need to return to one’s origins to better understand the present. On the other hand, we see a novel marked by the theme of duality, that speaks to us of not only exile, but also freedom and love – two mirrored stories that unfold through an alternating narrative between Europe and Afghanistan, where we feel “the infernal vertigo of the abyss that exile digs between words and thought” (Les porteurs d’eau, p. 72).